The Impact of Supply Chain Management in Service Quality Dimension on Patient Perception and Hospital Performance: Switching Cost as a Moderation - Mu’ah, Mu’ah; IkaPurwanti, IkaPurwanti; Sulton, Muhammad; Arifin, Mesra Surya (International Journal of Supply Chain Management, 2020)
Abstract- In this paper the concept of service quality in supply chain has been investigated in the health system. This article aims to fill the gap in the literature by providing evidence about patients’ satisfaction and loyalty regarding the health-care they experienced from Indonesia private hospitals by supply chain strategy. This research was conducted using the data from the consumers who received services from 4 different private hospitals in Surabaya, Indonesia. Core service quality and peripheral service quality (Service Quality dimensions), appraisal emotion and perceived value (Consumer Perception), patient satisfaction, loyalty (Hospital Performance, and switching cost to the hospital were the variables considered for this study. A path analysis was done on AMOS 23 in order to compute path coefficients, direct and indirect effects of the variables on patients’ satisfaction and also loyalty to the hospital. The result found that core service quality impacts patients’ satisfaction. The peripheral service quality has no significant effect on the patient’s satisfaction. Core service quality and peripheral service quality has a significant effect on appraisal emotion and perceived value. The appraisal emotion and perceived value have an impact on the patient’s satisfaction and loyalty. Patients’ satisfactionis directly related to patients’ loyalty to the hospital.